Tingkat kepadatan larva nyamuk Aedes aegypti di wilayah TPA Sukawinatan - Mareta, Oca; Hermansyah, Herry; Karneli (Tropis: Jurnal Riset Teknologi Laboratorium Medis, 2024)
Aedes aegypti mosquito is a competent vector for transmitting dengue fever which can live and reproduce in temporary water reservoirs such as drums, buckets, cans, tires, bottles and barrels such as those in the Sukawinatan TPA area RT.68 RW.10. This research aims to determine the density level of Aedes aegypti mosquito larvae in the Sukawinatan TPA area in 2023. This research is quantitative descriptive and uses primary data from a total sampling of 84 families at RT.68 RW.10 Sukawinatan TPA. The results show the level of density of Aedes aegypti mosquito larvae based on HI 28.57%, CI 10.85%, BI 48.81%, and larvae free rate 71.43%, DF obtained HI 5 (medium density), CI 4 (medium density). medium), and BI 5 (medium density). The HI, CI, BI, ABJ, and DF values ​​are still below the 2005 WHO standard, which means that the transmission of the Aedes aegypi mosquito is high. It is hoped that this research data can become a benchmark for evaluating the vector control program in the Sukawitan area, especially in TPA RT.68 RW.10, this can be anticipated by carrying out the PSN 3M Plus movement periodically which can be carried out by the community.